2003
DOI: 10.1111/j.1474-919x.2004.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of population declines of the Lesser Kestrel Falco naumanni in Israel

Abstract: We studied the ecology of the Lesser Kestrel Falco naumanni , a globally threatened species, to identify the factors causing its gradual decline in Israel, in order to stabilize and possibly restore its numbers. Lesser Kestrels in Israel breed in colonies, both adjacent to human settlements (rural and urban) and in the countryside, where they are found especially on cliffs. In this study, observations of Lesser Kestrels were carried out in three different breeding areas: (1) an urban colony in Jerusalem, (2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Whereas in the past planners, city municipalities, environmental organizations and ecologists were focused on conservation of wilderness areas, awareness of the importance of natural areas within cities, where most of the human population resides, is increasing (Breuste 2004, Liven-Schulman et al 2004, Bryant 2006. This is also true for the city of Jerusalem, where there is an active environmental community of local people from various organizations, that act to preserve the open spaces still remaining within and around Jerusalem (e.g.…”
Section: Implications For Planningmentioning
confidence: 96%
“…Whereas in the past planners, city municipalities, environmental organizations and ecologists were focused on conservation of wilderness areas, awareness of the importance of natural areas within cities, where most of the human population resides, is increasing (Breuste 2004, Liven-Schulman et al 2004, Bryant 2006. This is also true for the city of Jerusalem, where there is an active environmental community of local people from various organizations, that act to preserve the open spaces still remaining within and around Jerusalem (e.g.…”
Section: Implications For Planningmentioning
confidence: 96%
“…The lesser kestrel (Falco naumanni) is a secondary-cavity nester, that in most of its range, breeds in urban habitats Liven-Schulman et al, 2004) or in other man-made structures surrounded by open and dry cereal steppes (Serrano et al, 2001;Serrano and Tella, 2003;Franco et al, 2005;Sarà, 2010), where nests are found under roof tiles and inside balcony and wall crevices. Like most other Falco species, the lesser kestrel does not build a nest but lays its eggs directly on the cavity floor after scraping its substrate (Cramp and Simmons, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Although a cliff-nesting bird, it has taken the opportunity to breed in urban areas, surrounded by open landscapes (Serrano et al 2001, Serrano & Tella 2003, Franco et al 2005, Sarà 2010), particularly buildings. Although subject to some constraints (Liven-Schulman et al 2004), these man-made environments are likely to be more beneficial, compared to those of rural areas, due to increased food supply, decreased competition, and relatively low predation (Parker 1996, Tella et al 1996, Love & Bird 2000.…”
Section: Short Reportmentioning
confidence: 99%